The effect of non-dental glass fiber volume fraction on flexural strength of heat cured acrylic resin - Hadianto, Eko; Woroprobosari, Niluh Ringga; Mujaddid, Muhammad Difa Althof (Odonto : Dental Journal, 2022)
Background: Heat-cured acrylic resin is a material that is often used for the manufacture of removable partial dentures in dentistry because it uses simple equipment, relatively inexpensive, and is easy to repair. Acrylic resin also has a disadvantage, such as the low value of flexural strength so that it can cause the denture to fracture. This study determine the effect of non-dental glass fiber volume fraction on the flexural strength of heat cured acrylic resin.Method: This research are post-test only control group design. Acrylic resins were divided into four groups (6 sample each group), group 1 without the addition of non-dental glass fiber or 0% and heat cured acrylic resin group with the addition of non-dental glass fiber 1%,2%, and 3% (group 2, 3 and 4).Result: The average flexural strength of acrylic resin with a volume fraction of 2% of non-dental glass fiber had the highest value compared to other groups. The results of the Mann-Whitney test from several test groups showed significant differences in the value of flexural strength from each group (p<0.05), except for the 0% and 3% group.Conclusion: There is an effect of volume fraction of non-dental glass fiber on the flexural strength of heat cured acrylic resin.